Study of in vitro thrombin generation after neutralization of heparin. (28th September 2021) - Hardy, Michael; Douxfils, Jonathan; Morimont, Laure; Didembourg, Marie; Carlo, Audrey; de Maistre, Emmanuel; Lecompte, Thomas; Mullier, François
Abstract: Introduction: Thrombin generation (TG) documents hypercoagulability. TG in platelet‐poor plasma is exquisitely sensitive to heparins, which thus must be neutralized before testing. Heparinase and hexadimethrine bromide (polybrene) have been used for that purpose, but their effects per se on TG have been poorly studied so far. Methods: (i) TG was studied in commercial normal pooled plasma (NPP; CryoCheck ®, Cryopep) in absence or presence of neutralizing agents. (ii) NPP was spiked with increasing concentrations of unfractionated heparin (UFH; up to 1.0 IU/mL) or low‐molecular‐weight heparin (LMWH; enoxaparin up to 1.2 IU/mL) and TG studied after incubation of heparinase (Hepzyme ® ; 15 minutes) or polybrene (0.025 mg/mL; 10 minutes). Results: (i) With ThromboScreen reagent to initiate TG, addition of heparinase was associated with increased peak, whereas polybrene caused lengthening of lag time and time to peak, compared with nonsupplemented NPP. (ii) With polybrene, TG was completely restored over the whole range of UFH and LMWH studied. By contrast, heparinase failed to fully restore TG in presence of UFH concentrations ≥0.8 IU/mL or LMWH concentrations ≥1.0 IU/mL. Those effects were matched with detectable tiny residual amounts of non‐neutralized heparin (as assessed with an anti‐Xa assay) and were less pronounced with a higher picomolar concentration of tissue factor (DrugScreen reagent). Conclusion: Polybrene fully restored TG of heparinized plasma at the expense of an alteration of TG, pointing to the need to use adapted reference ranges. Heparinase failed to do so in presence of high concentrations of both heparins.